GERAKAN NU DALAM MEMAHAMI AJARAN ISLAM DARI TRADISIONALME KE POST TRADISIONALME - Mohammadong; Lukman (Cendekia, 2020)
The purpose of this research is for the traditional movement towards post traditionalism initiated by NU which is a form of renewal of thought in order to realize its existence in the state. The method used is a qualitative approach with a variety of literature review approaches related to NU and all aspects of its problems. The results show that the NU movement in understanding Islamic teachings is always consistent with its traditionalist culture so that it can develop into post-traditionalism teachings. The traditional movement that has been developed is a form of awareness of the nahdiyyin people to develop their own traditions as symbolism in order to apply quasi ideology. In the 2000s, NU's young intellectuals began to develop their thought studies into post-traditionalism to respond to current phenomena so that NU was able to take a role in advancing the State in an Islamic frame. The post-traditionalism that was initiated was not the antithesis of the traditional movement but as a form of integration in responding to the challenges of the times